Activated carbon as catalyst support: precursors, preparation, modification and characterization - Iwanow, Melanie; Gärtner, Tobias; Sieber, Volker; König, Burkhard (Beilstein Journal of Organic Chemistry, 2020)
The preparation of activated carbon materials is discussed along selected examples of precursor materials, of available production and modification methods and possible characterization techniques. We evaluate the preparation methods for activated carbon materials with respect to its use as catalyst support and identify important parameters for metal loading. The considered carbon sources include coal, wood, agricultural wastes or biomass as well as ionic liquids, deep eutectic solvents or precursor solutions. The preparation of the activated carbon usually involves pre-treatment steps followed by physical or chemical activation and application dependent modification. In addition, highly porous materials can also be produced by salt templating or ultrasonic spray pyrolysis as well as by microwave irradiation. The resulting activated carbon materials are characterized by a variety of techniques such as SEM, FTIR, nitrogen adsorption, Boehm titrations, adsorption of phenol, methylene blue and iodine, TPD, CHNS/O elemental analysis, EDX, XPS, XRD and TGA.
Keywords: activated carbon; catalysis; characterization techniques; metal supported on carbon catalysts; preparation methods